The missing piece [large type] - Lescroart, John T. (Lescroart, John T. Dismas Hardy novel, 2022)
"No one mourned with DA Wes Farrell put Paul Riley in prison for the rape and murder of his girlfriend. And no one is happy to see him when he's released after uncovered evidence pinned the crime on someone else. In fact, Riley soon turns up murdered. To the cops, it's straightforward: the father of Riley's dead girlfriend killed the former prisoner. Farrell, now practicing law with Dismas Hardy, agrees to represent the defendant--Doug Rush--and is left in the dust when his client suddenly vanishes. The search takes PI Abe Glitsky through a hall of mirrors populated by wounded parents, crooked cops, cheating spouses, and vigilantes"--